Guest editor - Hadjielias, Elias (My University, 2026)
Technovation (ABS3): Editor of Special Issue on “Systematic Literature Reviews: New Frontiers in Innovation Research” (due Dec 31st, 2021) https://www.journals.elsevier.com/technovation/call-for-papers/literature-reviews-new-frontiers-in-innovation-research